(NpOWERHNOSTNYE POLQRITONY W POLUPROWODNIKAH I DI\LEKTRIKAH (B/s - (NdMITRUK(B, (NnIKOLAJ lEONTXEWI^s; (NlITOW^ENKO(B, (NwLADIMIR gRIGORXEWI^s; (NsTRIVEWSKIJ(B, (NwLADIMIR lEONIDOWI^s; (NlISICA(B, (Nm(B.(Np(B.s; (NiNSTITUT POLUPROWODNIKOW an ussrs ((NkIEW (B:s (NnAUK(B. (NDUMKA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 347-371s
Keywords: (N|LEKTRI^ESTWOs